2022
DOI: 10.1186/s12960-021-00666-0
|View full text |Cite
|
Sign up to set email alerts
|

Application of workload indicators to assess the allocation of orthopedists in a national referral hospital in Brazil

Abstract: Background The study analyzes the allocation of specialized doctors’ orthopedists in a high-complex hospital, using the WHO’s Workload Indicators of Staffing Need (WISN) methodology and approach, which measures the workload pressure on the healthcare team (positive, negative, or well-adjusted). Methods In the first phase, the hospital’s operations and activities were analyzed using the information system. The duration of the tasks performed by the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 7 publications
0
0
0
Order By: Relevance
“…Documentary and health policy analysis is often used in workforce research [100,101] and cross-national comparisons of variations on regulation across jurisdictions are common in health workforce research [102,103], but were underused in the reviewed literature. The systematic review found no use of workload models and indicators [73], while these are commonly utilized for the continuous advancement of the nursing and other health professions [104][105][106][107].…”
Section: Discussionmentioning
confidence: 99%
“…Documentary and health policy analysis is often used in workforce research [100,101] and cross-national comparisons of variations on regulation across jurisdictions are common in health workforce research [102,103], but were underused in the reviewed literature. The systematic review found no use of workload models and indicators [73], while these are commonly utilized for the continuous advancement of the nursing and other health professions [104][105][106][107].…”
Section: Discussionmentioning
confidence: 99%